Obstructive sleep apnea and lung cancer: molecular underpinnings and clinical translational prospects - Zhang, Lin; Liu, Fengling; Li, Junyao (Frontiers in Cell and Developmental Biology, 2026)
Obstructive sleep apnea (OSA) is one of the most common sleep-disordered breathing conditions, characterized by repetitive narrowing or collapse of the pharyngeal airway, associated with chronic intermittent hypoxia (CIH), sleep fragmentation (SF), and sympathetic hyperactivity. Recent epidemiological surveys have shown that OSA may be associated with adverse outcomes, including various diseases and even death. In particular, its association with lung cancer has attracted widespread attention: on the one hand, OSA may promote tumor progression and reduce treatment sensitivity via core mechanisms such as chronic inflammation and oxidative stress; on the other hand, lung cancer itself and its related therapies can conversely exacerbate OSA, forming a complex bidirectional interplay that remains to be fully elucidated. This narrative review systematically searched PubMed and Web of Science databases for literature on OSA and lung cancer published up to September 2025, with a specific focus on mechanistic and clinical observational studies. It aims to clarify the inherent links between the pathophysiological features of OSA and the lung cancer tumor microenvironment (e.g., exosomes, tumor-associated macrophage polarization, and cancer stem cells), further shedding light on the underlying molecular mechanisms, and deepening the understanding of the pathogenic pathways driving OSA-associated lung cancer initiation and progression. Ultimately, this study aims to provide new insights into the clinical management of this comorbid condition and holds significant implications for improving the prognosis of patients with this condition.